Proceso atención de enfermería en neonato con ictericia fisiológica. - Quijije Espinoza, José Luciano (2021)
The nursing care process is a primary tool to provide appropriate care according to the needs of the patient, applying the PAE we establish specific care that will help the prompt recovery of the patient. Neonatal jaundice is characterized by the yellowing of the newborn due to the hyperbilirubin that the newborn presents very frequently within the first hours of life. This study was carried out at the San Miguel Basic Hospital, a 36-hour-old female newborn with a medical diagnosis of physiological neonatal jaundice, applying the taxonomies of NANDA, NOC and NIC, which favor the provision of specific care to the patient. patient according to their needs, contributing to the recovery of the newborn; The patient's case was followed up for 4 days of evaluation and control from the application of the ¨Phototherapy¨ treatment, after the application of the PAE in the care of the patient, a speedy recovery was achieved.